La crítica de Theodor W. Adorno al revisionismo neofreudiano - Fallas Vargas, Fabrizio (2005)
This paper explores Theodor W. Adornoʼs critique of the psychoanalytical tendencies that configure what is called “neofreudian revisionism”, fundamentally represented by Erich Frommʼs and Karen Horneyʼs theoretical attempts to establish a “revolution within psychoanalysis”. Accordingly, the study inquires about the young Adornoʼs reception of Freud, and his performance as a member of the Institute for Social Research in Frankfurt. Likewise, it assesses the scope of the self-proclaimed “neopsychoanalysis” and its capacity to achieve a critical insight into the organization of human existence in contemporary society.